A new ternary nanocomposites-based cellulose derivatives-CuFe2O4-zeolite with ultra-high adsorption capacity for Brilliant Green dye treatment and removal from the aquatic environment - Dina F. Katowah; Hanan K. Alzahrani (Journal of Saudi Chemical Society, 2023)
In contemporary times, there has been a notable emphasis on the advancement of adsorbents with high efficiency for the purpose of extracting organic dyes from wastewater. Therefore, a suggested method involves improving the surfaces of adsorbents by changing polymers in order to make them better at absorbing substances. The goal of this study was to create a very effective nanocomposite (NCs) by combining CuFe2O4 nanoparticles (CuF NPs) and zeolite (ZSM-5) with different types of cellulose, such as cellulose (CE), cellulose acetate (CEA), and carboxymethyl cellulose (CMC), in order to remove Brilliant Green (B.G.), a cationic dye, from water solutions. We investigated the influence of several factors on the efficacy of dye removal by NCs. These factors included the kind of cellulose derivative used, adsorbent dose, solution temperature, pH, and contact duration. The results of the prepared ternary ZSM-5/CuF/CE, ZSM-5/CuF/CEA, and ZSM-5/CuF/CMC NCs show that among the fabricated NCs, the ZSM-5/CuF/CE NCs have the highest adsorption capacity (9.66 mg/g). This result highlights the promising capability of these NCs in effectively removing B.G. dye. The results obtained from the studies on dye removal provided evidence that the adsorption process occurred spontaneously and exothermic, as supported by both thermodynamic and kinetic criteria. The values of the R2 correlation coefficient for ternary ZSM-5/CuF/CE and ZSM-5/CuF/CEA NCs for B.G. dye were 0.993 and 0.995, respectively.